2014
DOI: 10.11607/prd.1858
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Outcomes and Tissue Stability of Implant Placement in Compromised Sockets Following Immediate Dentoalveolar Restoration: Results of a Prospective Case Series at 58 Months Follow-up

Abstract: The aim of this prospective case series was to evaluate the stability of esthetic treatment after single tooth replacement in compromised sockets using the immediate dentoalveolar restoration (IDR) concept. Eighteen patients underwent immediate implant placement and IDR of bone defects. Clinical photographs were used to evaluate the gingival contour and papillae. The mean soft tissue dimensions at baseline and final follow-up were 12.85 ± 2.33 mm and 12.79 ± 2.48 mm, respectively, revealing no recession. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…Other technical features must also be prioritized, such as a minimally traumatic extraction, which can be carried out using extractor devices, for example 4 ; the use of implants with Morse type connection and switch platform, which minimize the formation of biofilm and prevent micromovements 18 ; and the use of smaller-diameter implants, thus maintaining maximum vascularization and nutrition in the bone bed 19 . Considering the position of the implant, an anchorage in the palatal wall of the alveolus, for the purpose of primary stability and creating distance between the implant and the buccal bone 8,18,20 is generally considered for better results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other technical features must also be prioritized, such as a minimally traumatic extraction, which can be carried out using extractor devices, for example 4 ; the use of implants with Morse type connection and switch platform, which minimize the formation of biofilm and prevent micromovements 18 ; and the use of smaller-diameter implants, thus maintaining maximum vascularization and nutrition in the bone bed 19 . Considering the position of the implant, an anchorage in the palatal wall of the alveolus, for the purpose of primary stability and creating distance between the implant and the buccal bone 8,18,20 is generally considered for better results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a less-invasive 4 approach is practiced in implantology due to the better understanding of bone biology and the development of new implants with surfaces that produce a better and quicker bone and peri-implant soft margin response, accelerating the rehabilitation. Thus, implants with immediate loading can be used in the majority of total, partial and even single rehabilitations [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to seal the extraction socket and support the tissues, the most commonly used option is an implant-supported provisional immediate restoration (Albiero, Benato, & Degidi, 2014;de Molon et al, 2015;Kan, Rungcharassaeng, Sclar, & Lozada, 2007;Noelken, Kunkel, & Wagner, 2011;Rosa, Rosa, Francischone, & Sotto-Maior, 2014;Tripodakis, Gousias, Mastoris, & Likouresis, 2016), despite some authors have resorted to using a tailor-made healing abutment to fit the gingival contour (Sarnachiaro, Chu, Sarnachiaro, Gotta, & Tarnow, 2016) or a removable provisional prosthesis suitably adapted (Assaf et al, 2017). On the other hand, to rebuild the buccal plate deficiency and filling the residual defect (or gap), some have only used a particulate graft consisting of autogenous bone chips (Noelken et al, 2011), particulate deproteinized bovine bone mineral (DBBM), with autogenous bone or not (Kan et al, 2007;Tripodakis et al, 2016), or a combination of platelet concentrates and allogeneic mineral bone (Norero & Ibanez, 2018), while others have used cancellous bone block grafts harvested from tuberosity (Rosa et al, 2014) or DBBM mini-blocks with collagen (Albiero et al, 2014;Assaf et al, 2017). Finally, some authors have identified the need to strengthen the connective tissue of the buccal plate combining an autogenous connective tissue with a cancellous bone block from the maxillary tuberosity to fill the gap (de Molon et al, 2015), or to improve the graft's stability and isolation using a collagen membrane (Sarnachiaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the nature of the available studies, these results must be cautiously assessed. Most cases involved a small number of patients (1-24) and a short follow-up period (under 2 years for six studies), despite 2 research papers report results at 5 years with particular techniques (Rosa et al, 2014;Tripodakis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Whenever a tooth must be removed and replaced by an implant it is important to limit the tissue losses and the collapse of the soft tissue after extraction [15]. If the patient's systemic and local conditions permit, an immediate implant and provisional can be placed in an intact or compromised socket to perform an immediate tooth replacement (ITR) [1618]. This procedure presents esthetical, psychological, functional, and biological advantages to the patient but must be well indicated in order to achieve treatment success [11, 12, 18, 19].…”
Section: Introductionmentioning
confidence: 99%